Safety and efficacy of cenobamate in patients with uncontrolled focal seizures - a review of the literature - Pietrzak, Zofia; Stefaniak, Martyna; Dzikowski, Piotr; Nowicka, Emilia; Obel, Michał; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2022)
Epilepsy is one of the most common diseases of the nervous system, characterized by the occurrence of recurrent and unprovoked seizures, which are an expression of abnormal brain activity associated with sudden and excessive bioelectric discharges. Partial seizures come from specific areas of the brain. They can run with motor, autonomic, sensory, and psychological symptoms. Currently, new active substances are sought that can be used in the treatment of drug-resistant partial seizures. The aim of the study is to evaluate the safety and efficacy of cenobamate in the treatment of patients with uncontrolled, partial seizures. Our study material consisted of publications, which were found in PubMed, Google Scholar, and Embase databases. In order to find the proper publications, the search has been conducted with the use of a combination of keywords like: “cenobamate”, “focal seizures”, “cenobamate in epilepsy”. The first step was to find proper publications from the last 10 years. The second step was to carry out an overview of the found publications. Studies have shown that treatment with cenobamate significantly improved seizure control in adults with uncontrolled focal seizures. Long-term use of cenobamate is safe and well-tolerated by patients. Most adverse events are mild or moderate.